Validating a model of strategic leadership practices for Malaysian vocational college educational leaders: a structural equation modeling approach - Mohd Ali, Hairuddin; Zulkipli, Inas (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this study is to conceptualize, validate and confirm a structural equation modeling (SEM) hypothesized model of strategic leadership practices of Malaysian vocational college educational leaders. Design/methodology/approach – The study used a quantitative survey approach. The data were collected from 500 educational leaders of 65 Malaysian vocational colleges throughout Malaysia using a fivepoint strategic leadership scale. The gender composition of the sample was almost equivalent. The study embarked on descriptive statistics, confirmatory factor analysis and full-fledged SEM for the data analyses. Findings – The findings revealed that the Malaysian vocational college educational leaders had high tendency and inclination of practicing strategic leadership at their workplace. Besides, there was also evidence that the educational leaders of the Malaysian vocational college exhibited high levels or degree of strategic leadership practices. The responses to the survey items were consistent with seven distinct practices of strategic leadership such as strategic orientation, strategic alignment, strategic intervention, restlessness, absorptive capacity, adaptive capacity and leadership wisdom. The use of SEM procedures had confirmed that the hypothesized model of strategic leadership practices for Malaysian vocational college educational leaders was empirically valid and reliable. Practical implications – The findings highlighted the importance of planning and development of a specific-context training program for Malaysian vocational college educational leaders in strategic leadership. The training was considered fundamental in pursuit of effective leadership and positive institutional outcomes for such colleges in Malaysia. Originality/value – The study had successfully formulated, tested and validated a model of strategic leadership practices for Malaysian vocational college educational leaders. The model was believed to be the first of its kind in the Malaysian vocational education context